Role of Absorptive Capacity in Predicting Continuance Intention to Use Digital Libraries: An Empirical Study - Hossain, ME; Bhuiyan, T; Mahmud, I; Ramayah, T; Scholtz, B (Springer, 2024)
The purpose of this paper is to investigate the impact of absorptive capacity and the quality dimensions of technology on students' continuance intention to use the e-library system. To measure the continuance intention, an integrated research model was developed using expectation-confirmation theory (ECT) and absorptive capacity theory. This empirical study was undertaken at a university in Bangladesh with a sample size of 297. Data was collected via a survey questionnaire. The results reveal that the dimensions of absorptive capacity have a strong effect on confirmation of the system and a partial impact on perceived usefulness (PU). Confirmation of the system has a significant effect on the PU of and satisfaction with the system. Satisfaction was found to be a strong predictor for the continuance intention to use the e-library. Finally, ECT fully fits in this context and students' satisfaction has the largest effect on the continuance intention.